Synthesis, Photophysical, Electrochemical Properties and Anticancer, Antimicrobial Activity of N‐n‐Hexyl‐N‐Phenylanilinochalcone‐Capped Dendrimers. Issue 31 (6th November 2017) - Ravivarma, Mahalingam; Rajakumar, Perumal
Abstract: Dendrimers with N ‐n‐hexyl‐ N ‐phenylanilinochalcone as surface group and triazole as bridging unit were synthesized in good yields. UV‐Visible absorption spectrum of N ‐n‐hexyl‐ N ‐phenylanilinocalcone dendrimers show two intense absorption bands at 277–297 and 419 nm and the molar extinction coefficient of the dendrimers increases with increase in the dendrimer generation. In emission spectrum, the chalcone dendrimers show a red shift of 10 nm for the first generation dendrimers when compared to the corresponding zeroth generation dendrimers. In cyclic voltammogram, all the dendrimers show quasi‐reversible redox peaks. N ‐n‐Hexyl‐ N ‐Phenylanilinochalcone dendrimers show better cell viability (≈55%) even at higher concentration against normal liver cell line. The cytotoxicity of the chalcone dendrimers were carried out on A549 lung adenocarcinoma cell lines at various concentrations. The cytotoxicity of the chalcone dendrimers was found to be dose dependent. The higher generation fluorene and benzene core chalcone dendrimers with more number of chalcone units show significant anticancer activity. Interestingly, all the chalcone dendrimers exhibit significant antimicrobial activity against the tested pathogenic microbes. Abstract : Synthesis of dendrimers with N ‐n‐hexyl‐ N ‐phenylanilinocalcone as surface group and triazole as bridging group. The photophysical studies shows that as the generation of the dendrimer increases light absorbing capacity also increases. In electrochemical studies, the dendrimers show quasi‐reversible redox peaks. The first generation fluorene and benzene core chalcone dendrimers showed better anticancer activity against human lung cancer (A549) cell line. Dendrimers exhibit significant antimicrobial activity against the tested pathogenic microbes.